Making Sense of Bad English : An Introduction to Language Attitudes and Ideologies. - Peterson, Elizabeth (Milton : Taylor & Francis Group, 2019)
Making Sense of "Bad English" is an accessible introduction to attitudes and ideologies towards the use of English around the world. The book provides an engaging and thought-provoking overview of this topic and is essential reading for any student studying sociolinguistics within a global setting.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books